Pengaruh Diameter Media Filtrasi Zeolit Terhadap Turbidity, Total Disolved Solids Dan Total Suspended Solids Pada Reaktor Filter - DODIT ARDIATMA (DPPM Universitas Pelita Bangsa, 2020)
Most of the groundwater in the Pasirlimus village area is yellow, which is thought to have the turbidity level exceeding the threshold, so it is necessary to treat it so that the ground water meets the requirements for clean water quality. Groundwater is treated using a slow sand filter reactor with a single zeolite sand filter media with variations in the diameter of the sand measuring 0.1 - 0.25 mm, 0.25 - 0.5 mm and 0.5 - 1.0 mm. This type of research is quantitative with experimental instruments. The sampling technique in this study was grab sampling with sampling based on the diameter of the zeolite in the filter reactor and then the sample was tested in the laboratory. Based on the results of laboratory analysis, the percentage reduction in turbidity, total dissolved solids, and total suspended solids using variations in the diameter of the zeolite filtration media 0.1 - 0.25 mm, 0.25 - 0.5 mm, 0.5 - 1.0 mm in the reactor diameter 0.1 - 0.25 mm 94% of turbidity parameters , 90% total suspended solids parameter, 90% total suspended solid. Media diameter 0.25 - 0.5 mm is 64% turbidity, while Total Disolved Solids is 84% ​​and total suspended solid is 73%. 1.0 - 2.0 mm is 10% turbidity, while total dissolved solids is 16% and total suspended solid is 14% and the coefficient of determination (R2) of turbidity using a variation of diameter at a concentration of 283 NTU is 0.9996, TDS at a concentration of 791 mg / L is 0.9134, TSS at a concentration of 82 mg / L is 0.9722.